Tropical ecosystems and ecological concepts - Osborne, Patrick L. (Cambridge University Press, 2012)
"Tropical habitats cover over one third of the Earth's terrestrial surface and harbor much of its biodiversity, with many areas rich in endemic species. However, these ecosystems are under significant and growing threat from issues such as deforestation, land degradation and ocean acidification. This introductory textbook provides a comprehensive guide to the major tropical biomes. It is unique in its balanced coverage of both aquatic and terrestrial systems and in its international scope. Each chapter is built around a particular tropical ecosystem, with descriptive case studies providing a framework around which ecological concepts and applied ecological topics are presented. This second edition has been thoroughly updated to reflect recent advances in the field and includes a greater focus on the impact of global climate change. The text is supported throughout by boxes containing supplementary material and is illustrated with over 200 clear, simple line diagrams, maps and photographs"--Provided by publisher.